The Food Resources and Kitchen Skills intervention: Protocol of a randomized controlled trial. - Armando Peña; Emily Dawkins; Mariah Adams; Lyndsi R Moser; Amy Carter; Rebecca L Rivera; Deanna Reinoso; Wanzhu Tu; Richard J Holden; Daniel O Clark (PLoS ONE)
Introduction Individuals with food insecurity are disproportionately burdened by hypertension (HTN) and type 2 diabetes and face greater barriers to self-managing these conditions. Methods Food Resources and Kitchen Skills (FoRKS) is an ongoing 2-arm parallel randomized controlled trial (RCT) that will enroll 200 adults (35-75 y) with food insecurity and elevated systolic blood pressure (≥120 mmHg) at a large federally qualified health center (FQHC) network in Central Indiana. Blood pressure is measured using an ambulatory blood pressure monitoring (ABPM) device. The (FoRKS, N = 100) intervention integrates hypertension self-management education and support (SMES) with a home-delivered ingredient kit and cooking skills program (16 weeks). Enhanced Usual Care (EUC, N = 100) includes usual care services by the FQHC network, SMES classes (separate from FoRKS), and grocery assistance. This paper describes the protocol for this RCT that will: 1) test the efficacy of FoRKS compared to EUC for reducing systolic blood pressure using an intention to treat protocol, 2) identify behavior change levers (e.g., engagement, social support) and their associations with change in food insecurity, diet quality, and systolic blood pressure, 3) examine the maintenance of outcomes, and 4) assess cost-effectiveness. Conclusions Establishing that a food insecurity and SMES intervention, compared to usual care services, is feasible in FQHCs and efficacious for improving blood pressure and related outcomes would have important public health implications. Understanding the behavior change levers of FoRKS that are associated with changes in health outcomes, whether these outcomes are maintained, and its cost-effectiveness will inform future efforts to address health disparities.